The muslims as a minority in New Zealand : an analysis of the relationship between muslim community and New Zealand government - Nawaz, Tahir (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This study delves in depth into the Muslims as a minority and the analysis of their relationship with the government of New Zealand. The study starts with the overview of Islam and related background on Islam in New Zealand, then the historical inquiry into Muslims in New Zealand, which was traced back to 1850s, followed by a discussion on Islamic organisations in New Zealand and their chronological description. After that, the research further shares an insight into the relationship that existed between Muslim community and New Zealand Government. However, in the course of the fieldwork carried out by the researcher, and due to the feedback as well as broad events around the globe, it was clear that, there is misunderstanding in most Western countries about Muslims, and there is silent hostility towards Islam due to colonial racial discrimination and orientalism. Although, New Zealand is different as it encourages religious diversity, cultural differences and ethnic community in acknowledgement of the “Waitangi treaty” of 1840. The findings also suggested that the Muslim community should continue to formulate a better working relationship with NZ government for safer and peaceful society.